Dampak Kausal Pendidikan terhadap Pernikahan di Indonesia: Temuan Empiris dari Pendekatan Sharp Regression Discontinuity Design: Institut Pertanian Bogor - Hasanah, Heni (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
The marriage rate in Indonesia has declined over the past six years, with the percentage of young people (aged 16–30) who remain unmarried showing a consistent upward trend. This trend can have positive implications if it is driven by a decrease in early marriages; however, it may also have negative consequences, particularly in terms of demographic challenges. Among the many factors influencing an individual's decision to marry, this study focuses on analysing the impact of education on marriage. Education plays a critical role in shaping various aspects of an individual's life, including decisions related to marriage. The data used in this study comes from the 2007 Indonesian Family Life Survey (IFLS) and employs a sharp Regression Discontinuity Design (RDD) approach to estimate the impact. The policy change of the new school year in 1978, used as an exogenous variable, serves as a proxy for years of education with the aim of minimizing potential bias in the estimation results. The study's findings show that longer years of education have an impact on increasing the age at first marriage. The results of this study indicate that education has the potential to serve as an effective intervention tool to delay marriage in relation to reducing the rate of early marriages. However, special attention is also needed regarding the potential negative impacts of delaying marriage on long-term demographic issues.